2011
DOI: 10.3763/ijas.2010.0554
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural success from Africa: the case of fertilizer tree systems in southern Africa (Malawi, Tanzania, Mozambique, Zambia and Zimbabwe)

Abstract: In response to the declining soil fertility in southern Africa and the negative effects that this leads to, such as food insecurity besides other developmental challenges, fertilizer tree systems (FTS) were developed as technological innovation to help smallholder farmers to build soil organic matter and fertility in a sustainable manner. In this paper, we trace the historical background and highlight the developmental phases and outcomes of the technology. The synthesis shows that FTS are inexpensive technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 26 publications
1
33
0
3
Order By: Relevance
“…These include improved soil and water conservation methods (e.g., Fowler and Rockström 2001;Hobbs et al 2008;Erenstein et al 2012), integrated nutrient management (e.g., Vanlauwe et al 2010;Timsina et al 2010Timsina et al , 2011, the retention and use of biodiversity on crop fields (Mapfumo et al 2005;Snapp et al 2010) and the improved management of farm fields with different nutrient status (e.g., Giller et al 2006;Tittonell et al 2008). Across Sub-Saharan Africa, many of the more-traditional maize systems maintain productivity while reducing abiotic and biotic environmental impacts by intercropping or rotating leguminous trees and shrubs, and annual legumes with maize (Snapp et al 1998(Snapp et al , 2010Waddington et al 2007;Ajayi et al 2011;Pretty et al 2011), or by incorporating legume weed residues into croplands (Mapfumo et al 2005). The expansion of such practices should be encouraged.…”
Section: Good Practices To Manage Crop X Environment Interactionsmentioning
confidence: 99%
“…These include improved soil and water conservation methods (e.g., Fowler and Rockström 2001;Hobbs et al 2008;Erenstein et al 2012), integrated nutrient management (e.g., Vanlauwe et al 2010;Timsina et al 2010Timsina et al , 2011, the retention and use of biodiversity on crop fields (Mapfumo et al 2005;Snapp et al 2010) and the improved management of farm fields with different nutrient status (e.g., Giller et al 2006;Tittonell et al 2008). Across Sub-Saharan Africa, many of the more-traditional maize systems maintain productivity while reducing abiotic and biotic environmental impacts by intercropping or rotating leguminous trees and shrubs, and annual legumes with maize (Snapp et al 1998(Snapp et al , 2010Waddington et al 2007;Ajayi et al 2011;Pretty et al 2011), or by incorporating legume weed residues into croplands (Mapfumo et al 2005). The expansion of such practices should be encouraged.…”
Section: Good Practices To Manage Crop X Environment Interactionsmentioning
confidence: 99%
“…In addition, agroforestry is known for providing benefits to the environment by providing various ecosystem services (Sileshi et al 2007, Bhagwat et al 2008, Jose 2009, Nair et al 2009). For example, Ajayi et al (2011) have shown that fertilizer tree systems are inexpensive technologies that significantly raise crop yields, reduce food insecurity and enhance environmental services and resilience of agro-ecologies in southern Africa. Although the benefits of agroforestry are well known and various innovations are being used by farmers throughout the tropics, widespread adoption has not occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies have shown that both regenerative and planted tree systems can be profitable (for examples see Ajayi et al 2007;Ajayi et al 2011;. Planted systems require more labor, not only for establishment of trees but also for management of potential competition with crops, especially when exotic fast-growing tree species are used.…”
Section: Improved Soil Fertilitymentioning
confidence: 99%